2014
DOI: 10.3748/wjg.v20.i33.11916
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of neuroendocrine carcinoma of the gallbladder

Abstract: Neuroendocrine carcinoma (NEC) of the gallbladder is a rare subtype of gallbladder tumor. Here, we report two cases of NEC in two patients initially suspected to have gallbladder carcinoma. No specific symptoms or abnormal blood test results were observed preoperatively. Abdominal computed tomography scans indicated intraluminal masses in the gallbladder and lymph node enlargement in the hepatic hilum. Radical cholecystectomy and regional lymphadenectomy were performed. The first patient also presented with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…The definite diagnosis is based on immunohistochemical expression of marker proteins. In our two patients, immunohistochemical analysis showed that tumor cells were negative for cytokeratin and vimentin and positive for CD 56, chromogranin A and synaptophysin, thus supporting the final diagnosis of neuroendocrine tumor [2,3,9].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The definite diagnosis is based on immunohistochemical expression of marker proteins. In our two patients, immunohistochemical analysis showed that tumor cells were negative for cytokeratin and vimentin and positive for CD 56, chromogranin A and synaptophysin, thus supporting the final diagnosis of neuroendocrine tumor [2,3,9].…”
Section: Discussionmentioning
confidence: 85%
“…In some reports, the tumor itself was not visible at imaging and was found incidentally during histopathological analysis of resected specimen after surgical resection of the gallbladder for another reason that the tumor itself [4][5][6]. In other cases, the tumor presented as an irregular, circumferential thickening of the gallbladder [2] or as an intraluminal polypoid mass [2,3,7] similar to the findings observed in the more common adenocarcinoma of the gallbladder [6,8]. Primary neuroendocrine tumors of the gallbladder may also present as chronic cholecystitis with circumferential, homogeneous thickening of the gallbladder wall with intraluminal stones [9].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations